Australian Election Study, 1993 - Jones, Roger (ADA Dataverse, 2017)
The 1993 Australian Election Study is the third in a series of surveys beginning in 1987 which have been timed to coincide with Australian Federal elections. The series also builds on the 1967, 1969 and 1979 Australian Political Attitudes Surveys. The Australian Election Studies aim to provide a long-term perspective on stability and change in the political attitudes and behaviour of the Australian electorate, and investigate the changing social bases of Australian politics as the economy and society modernise and change character. In addition to these long-term goals they examine the political issues prevalent in the election and assess their importance for the election result. The 1993 survey replicates many questions from the 1987 and 1990 Australian Election Studies, but also introduces a variety of new questions including a section on foreign affairs and defence, and attitudes to Federal and State government. As in previous surveys, other sections covered the respondent's interest in the election campaign and politics, their past and present political affiliation, evaluation of parties and candidates, alignment with parties on various election issues, evaluation of the economic situation and economic policies, attitudes to a range of environmental issues, and attitudes to contemporary social policy issues including equal opportunity, censorship, migration, assistance for aborigines, abortion, criminal law, expenditure on social services, the monarchy and the Australian flag. Background variables covered include level of education, employment status, occupation, type of employer, position at workplace, trade union membership, sex, year and place of birth, parents' birthplaces, parents' political preferences, father's occupation, length of residence in state or territory, religion, marital status, number of children, income, and where applicable, the occupation, trade union membership and political preference of the respondent's spouse.